Active anti‐islanding detection based on pulse current injection for distributed generation systems. Issue 8 (1st September 2013) - Hou, Chung‐Chuan; Chen, Yu‐Chun
Abstract : This study proposes an active anti‐islanding detection using an adjustable pulse current for distributed generation systems. The pulse current injection is utilised to find out difference voltage response between utility systems and islanding operation systems within 2.8 ms, which is faster than conventional current injection methods. Furthermore, the power line communication is utilised to keep islanding detection system with accuracy. Finally, the performances of the proposed scheme are validated by simulation and test results.